Excretion and clearance of Sabin-like type 3 poliovirus in a child diagnosed with severe combined immunodeficiency - Ning Yao; Yang Liu; Zhi-Yong Zhang; Min Tian; Wu-Juan Xie; Hua Zhao; Hong Yang; Lance E. Rodewald; Ning Wen; Zun-Dong Yin; Fu-Zhen Wang; Qing Wang; et al. (Human Vaccines & Immunotherapeutics)
Children with primary immunodeficiency disorder (PID) are at higher risk of developing vaccine-associated paralytic poliomyelitis (VAPP) or vaccine-derived polioviruses (VDPV) infection when inadvertently expose to poliovirus vaccine, oral (OPV). A pilot study was initiated to describe the epidemiology of immunodeficiency-associated VDPV (iVDPV) and to estimate the risk of iVDPV shedding among individuals with PID. Children under 18 years of age newly diagnosed with PID were recruited for investigation and tested for poliovirus excretion. Children with poliovirus-positive stool samples had regular follow-up testing for poliovirus excretion and determination of clinical prognosis. A patient with severe combined immunodeficiency (SCID) with compound heterozygous mutations in the RAG1 gene was found to be excreting Sabin-like type 3 (SL3) poliovirus. Excretion stopped six weeks after hematopoietic stem-cell transplantation (HSCT). Graft versus host disease (GVHD) and poor graft function (PGF) occurred after HSCT, resulting in failure of hematopoiesis and immune system reconstitution. Given deficient innate and adaptive immunity, immune-mediated destruction of gastrointestinal (GI) tract caused by GVHD and inflammatory diarrheal illness of the girl may have contributed to her clearance of SL3 poliovirus. Intermittent surveillance of immune system parameters for iVDPV excreters receiving HSCT should be included in the PID surveillance program for further understanding poliovirus clearance mechanisms.